2017
DOI: 10.1371/journal.pone.0185335
|View full text |Cite
|
Sign up to set email alerts
|

Shark Spotters: Successfully reducing spatial overlap between white sharks (Carcharodon carcharias) and recreational water users in False Bay, South Africa

Abstract: White sharks (Carcharodon carcharias) are apex predators that play an important role in the structure and stability of marine ecosystems. Despite their ecological importance and protected status, white sharks are still subject to lethal control to reduce the risk of shark bites for recreational water users. The Shark Spotters program, pioneered in Cape Town, South Africa, provides a non-lethal alternative for reducing the risk of human-shark conflict. In this study we assessed the efficacy of the Shark Spotter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 31 publications
1
23
0
3
Order By: Relevance
“…To address a growing public concern (Nel and Peschak, 2006), the City of Cape Town and partners have employed shark spotters at eight of its beaches to provide an early warning system for recreational water users (Kock et al, 2012), as well as a shark exclusion net at Fish Hoek (Kock and O'Riain, 2015). Research has demonstrated that this program is an effective way to reduce the spatial overlap between people and sharks in time and space, thus reducing the chance of negative encounters, which have the potential to affect the number of ocean users up to three months following a fatal incident (Engelbrecht et al, 2017).…”
Section: Human-wildlife Conflictsmentioning
confidence: 99%
“…To address a growing public concern (Nel and Peschak, 2006), the City of Cape Town and partners have employed shark spotters at eight of its beaches to provide an early warning system for recreational water users (Kock et al, 2012), as well as a shark exclusion net at Fish Hoek (Kock and O'Riain, 2015). Research has demonstrated that this program is an effective way to reduce the spatial overlap between people and sharks in time and space, thus reducing the chance of negative encounters, which have the potential to affect the number of ocean users up to three months following a fatal incident (Engelbrecht et al, 2017).…”
Section: Human-wildlife Conflictsmentioning
confidence: 99%
“…Initially, these programs focused solely on localised reduction of shark numbers using mesh nets and a system of large baited hooks suspended from surface floats, known as 'drum lines', to catch and kill sharks (Cliff and Dudley 2011;Reid et al 2011;Sumpton et al 2011). Gradually, increasing public concern over the programs' impacts upon both by-catch (typically non-target elasmobranchs, marine mammals and reptiles) and target species has seen governments searching for measures that improve protection for swimmers while minimising the impacts on sharks and other marine wildlife (Cliff and Dudley 2011;Hazin and Afonso 2014;Engelbrecht et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of identifying and implementing broadly applicable and cost-effective shark deterrents has given rise to measures aimed at shark detection (with subsequent warnings to swimmers) rather than deterrence. Detection approaches include trained observers working from elevated coastal vantage points (Engelbrecht et al 2017), automated sonar systems (McPhee and Blount 2015;Parsons et al 2015), acoustic tagging and monitoring programs (McAuley et al 2016) and manned aerial patrols using fixed-wing aircraft or helicopters (McPhee and Blount 2015;Robbins et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Public expectations of being safe from sharks when undertaking marine activities require a better understanding of human-shark interactions, effectiveness of current mitigation measures, and improved public education outreach. Long-term databases (e.g., International Shark Attack File; Shark Spotters) provide an opportunity to delve further into patterns in shark bites and human-shark spatio-temporal overlap for management of human-shark interactions (Engelbrecht et al, 2017). This could lead to improved ability to predict shark occurrence and the likelihood of a shark bite (Ferretti et al, 2015).…”
Section: Can We Reliably Assess and Significantly Reduce Human-shark mentioning
confidence: 99%